The Democratic Anomaly in 2020 Regional Head Elections (PILKADA) with a Single Candidate in Semarang City - Susanti, Martien Herna; Setiajid, Setiajid (Political Science Program, Universitas Negeri Semarang, 2022)
This research aims to describe the democratic anomaly in the election of a single candidate in the city of Semarang and the deception background factors of the victory of the incumbent in the election of a single candidate in Semarang City in 2020. This study uses a qualitative descriptive design. The research location is in Semarang City. The research focus includes incumbent capabilities in the regional head elections in 2020. The sampling techniques used are purposive sampling and snowball sampling. Research informants encompass the success team of candidate pairs and the people of Semarang City. Research data was collected through interviews, Focus Group Discussion (FGD), and documentation study. Data validity was tested using data triangulation and analyzed using interactive qualitative analysis techniques. The study results show that many groups have predicted the existence of a single candidate in the 2020 Semarang City Election. Considering the incumbent's achievements while serving as mayor of Semarang, a single candidate as a democratic anomaly is accepted as a natural thing. Some factors determine the incumbent’s victory—first, political capital. The incumbent's ability to bring the City of Semarang to win various awards creates a sense of satisfaction from the public and political parties for his leadership performance while in office. Second, ocial capital. Incumbents are very popular in Semarang City, so they have high electability. Third, the economic capital. Incumbents benefit more financially, especially when it comes to the issue of campaign costs, to gain support for their victory.